2011
DOI: 10.1128/jb.05199-11
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Spo0A by the Histidine Kinase KinD Requires the Lipoprotein Med in Bacillus subtilis

Abstract: The response regulatory protein Spo0A of Bacillus subtilis is activated by phosphorylation by multiple histidine kinases via a multicomponent phosphorelay. Here we present evidence that the activity of one of the kinases, KinD, depends on the lipoprotein Med, a mutant of which has been known to cause a cannibalism phenotype. We show that the absence of Med impaired and the overproduction of Med stimulated the transcription of two operons (sdp and skf) involved in cannibalism whose transcription is known to dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…KinD also seems to be important in B. subtilis colonization on the plant host by sensing plant-released signals and promoting biofilm formation on the root surface of the plant (19). It was also recently suggested that the activity of KinD depends on its partner, a lipoprotein termed Med (41). Based on the above-described studies as well as the present study, we suppose that the signalsensing ability of KinD is multifaceted.…”
Section: Discussionmentioning
confidence: 62%
“…KinD also seems to be important in B. subtilis colonization on the plant host by sensing plant-released signals and promoting biofilm formation on the root surface of the plant (19). It was also recently suggested that the activity of KinD depends on its partner, a lipoprotein termed Med (41). Based on the above-described studies as well as the present study, we suppose that the signalsensing ability of KinD is multifaceted.…”
Section: Discussionmentioning
confidence: 62%
“…To investigate whether the root exudate was stimulating Spo0A∼P activity, we used a luciferase gene fusion to the promoter for the sdpABC operon (P sdpA ‐ lux ), whose activity is known to be highly sensitive to Spo0A∼P levels (Banse et al ., 2011). Addition of 1% root exudate to the medium increased expression of the P sdpA ‐ lux reporter fusion by about twofold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 in 3E4P and 3E4Q (DctB 29,30 ), 174.4 in KinD-SD (this work), 176.2 in 3C8C, 32 179.2 in 3T4J 34 and 180 in 3LIA, 3LI8, and 3LI9. 31 In 3LI8…”
Section: Comparison Of Periplasmic Sensors Composed Of Tandem Pas-likmentioning
confidence: 99%